2019
DOI: 10.3390/app9224956
|View full text |Cite
|
Sign up to set email alerts
|

Security Analysis of Discrete-Modulated Continuous-Variable Quantum Key Distribution over Seawater Channel

Abstract: We investigate the optical absorption and scattering properties of four different kinds of seawater as the quantum channel. The models of discrete-modulated continuous-variable quantum key distribution (CV-QKD) in free-space seawater channel are briefly described, and the performance of the four-state protocol and the eight-state protocol in asymptotic and finite-size cases is analyzed in detail. Simulation results illustrate that the more complex is the seawater composition, the worse is the performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…Bouchard suggested a high dimensional BB84 protocol with twisted photons in outdoor conditions [ 20 ]. After that Ruan proposed a method to estimate parameters to improve CVQKD performance [ 21 ]. However, the implementation of MDI-QKD underwater has been waiting for some researches to fill the gaps.…”
Section: Introductionmentioning
confidence: 99%
“…Bouchard suggested a high dimensional BB84 protocol with twisted photons in outdoor conditions [ 20 ]. After that Ruan proposed a method to estimate parameters to improve CVQKD performance [ 21 ]. However, the implementation of MDI-QKD underwater has been waiting for some researches to fill the gaps.…”
Section: Introductionmentioning
confidence: 99%
“…While mastering the basic protocol of DM-CV-QKD, its application range can be expanded according to its characteristics. It has the potential for communications in free-space channels (Hill et al, 2017;Mélen et al, 2017), satellite-to-earth channels (Liao et al, 2017a) and seawater channels (Ruan et al, 2019). In addition, MDI protocols against side-channel attacks and device-independent protocols with higher security are also worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, aim of this approach is to generate high key rates for longer distances as well. Ruan et al 188 analyzed optical absorption and scattering properties of discrete‐modulated CV‐QKD. It is observed that the performance of four and eight‐state protocol in asymptotic and finite‐size cases is dependent on seawater composition, that is, if the composition is complex, then the performance of protocol decreases as well.…”
Section: Quantum and Post‐quantum Cryptographymentioning
confidence: 99%